2005
DOI: 10.5194/angeo-23-1611-2005
|View full text |Cite
|
Sign up to set email alerts
|

Relative drift between black aurora and the ionospheric plasma

Abstract: Abstract. Black auroras are recognized as spatially welldefined regions within uniform diffuse aurora where the optical emission is significantly reduced. Although a well studied phenomenon, there is no generally accepted theory for black auroras. One theory suggests that black regions are formed when energetic magnetospheric electrons no longer have access to the loss cone. If this blocking mechanism drifts with the source electron population in the magnetosphere, black auroras in the ionosphere should drift … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 27 publications
3
16
0
Order By: Relevance
“…Two black aurora events, one of which is shown in Figure , showed black arc segments or patches drifting eastward with a noticeable velocity, which matches previous studies [ Trondsen and Cogger , ; Peticolas et al , ; Blixt et al , ]. The drift speeds measured are on the order of 15 km/s, much higher than previous reports like Blixt et al [] who reported a maximum drift of 4 km/s.…”
Section: Observationssupporting
confidence: 89%
“…Two black aurora events, one of which is shown in Figure , showed black arc segments or patches drifting eastward with a noticeable velocity, which matches previous studies [ Trondsen and Cogger , ; Peticolas et al , ; Blixt et al , ]. The drift speeds measured are on the order of 15 km/s, much higher than previous reports like Blixt et al [] who reported a maximum drift of 4 km/s.…”
Section: Observationssupporting
confidence: 89%
“…There were several large morphological studies of black aurora in the 1990s, describing its characteristics and features (such as, Schoute-Vanneck et al, 1990;Trondsen and Cogger, 1997;Kimball and Hallinan, 1998). More recent studies, using satellites (Peticolas et al, 2002), and radars (Blixt and Kosch, 2004;Blixt et al, 2005) have linked the generation of black aurora to a magnetospheric origin. Therefore its presence in ground-based auroral images can be used to gain information about in situ processes and assist in interpreting combined in situ data.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of such systems are the mobile, campaign-oriented instruments Portable Auroral Imager (PAI) of the University of Calgary and the Odin (Optical Digital Imager) of the University of Tromsø (Blixt et al, 2005b). With a 50 mm lens the maximum resolution at 105 km altitude is better than 40 m. When emissions are weak, integration may be needed.…”
Section: Ground-based Imagersmentioning
confidence: 99%
“…10. Blixt et al (2005b) then investigated the drift of black patches. In seven of the eight events studied the patches drifted eastward with velocities of 1.5-4 km/s.…”
Section: Black Auroramentioning
confidence: 99%